The Influence Of Service Inclusivity On The Comfort Of Sidilan FISIPOLUnesa Website Users - Krisna Dwi Darna Iswanto; Fitrotun Niswah; Meirinawati M; Eva Hany Fanida (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The digital transformation in higher education requires services that are not only effiicient and effective but also inclusive and accessibke to all users. This study aims to analyze the influence of service inclusivity on user convenience on the Digital Service System (Sidilan) website of the Faculty of Social and Political Sciences, UNESA. A quantitative approach was employed using a survei method involving Sidilan Website users. The collected data were analyzed using inferential statistic through simple linear regression analysis. The results indicate that service inclusivity has a positive and significant effect on user convenience, with a significance values of less that 0,001. Regarding user convenience dimensions, all dimensions of service inclusivity significantly affect access convenience and evaluation convenience. However, in the search convenience dimension, the availibility variable was not significant (Sig. 0,290). Likewise, in service submission convenience and post-submission convenience, the affordability variable showed no significant effect, with significance values of 0,059 and 0,099, respectively. The findings also reveal that digital ability is the most dominant dimension influencing all aspects of user convenience, as indicated by the highest Beta coefficient of  0,513 in the search convenience dimension. These findings suggest that improving the quality of inclusive digital services should be accompanied by strengthening user’s digital capabilites to ensure that services can be accessed, understood, and utilized effectively by all members of the academic community without barriers.